An Empirical Study On Real Exchange Rate Levels And The Role Of Macro-economic Indicators: Evidence From Algeria - Maachi, Malika (جامعة الوادي- University of Eloued, 2016)
The purpose of this study is reviewing the real exchange rate RER evolutions and measuring their macroeconomic impacts on the economic performance indicators during the period from 1970 to 2012, also determining the trend of those impacts and their influence nature on the Algerian economy applying modern econometric methods as Error Correction Model, Johansen Cointegration Approaches and Ordinary Least Squares OLS to estimate the last formulation of the relation between used variables. The extracted econometric results, affirm the existence of a cointegration relationship between the RER and the macro variables of economy in general and with the Algerian economy in particular. More specifically and according to these results the association between the RER and the gross domestic product GDP, the investment INV, the index ofopenness OPEN and the financial sector developmentFD is significantly positive but significantly negative with both inflation INF and theindex of political stability POLSTAB, while its relation to government GOV is insignificant.
مقال
Keywords: Real Exchange Rate (RER), economic performance indicators, Cointegration test, Error Correction Modelling, Ordinary Least Squares.